Application of Value Stream Mapping on Operating Project Business Process at Nickel Mining Industry - Aristo Andryanto; Iwan Vanany (Institut Teknologi Sepuluh Nopember, 2020)
This study investigated the usage of manhours against project cost impact in the business process of capital and operating project in mining industry. The case study in this study is nickel mining company in Indonesia. The waste identification and elimination are used on the business process operations and capital project delivery system using lean thinking in project management and Analytical Hierarchy Process (AHP). The study results shows that in current business process state, 95% project expenditure in case study on 2019 was spent for capital project and 5% for project operations. This results of this study is quite different with the manhours spent each on operating and capital project. In 2019, both the Capital Project Management and Engineering Services department spent 70% of their manhours on Capital Project and 30% on Operating Project. It shows that in managing 5% of their project budget, the company’s case study had to spent 30% of their project team manhours. With the proposed business process, the company’s case study should be able to optimize their manhours usage proportionally to the project cost impact.